MEMBANGUN BUDAYA LITERASI BAGI GURU DAN KEPALA SEKOLAH PROFESIONAL PADA ERA REVOLUSI INDUSTRI 4.0 - Oktarina, Ririn (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This article describes how to build a literacy culture for teachers and principals to be more professional in working in the current era of industrial revolution 4.0. Literacy culture is very necessary to face the era of industrial revolution 4.0 which is characterized by increasing interaction between humans, machines and other resources through information and communication technology. In the era of revolution 4.0, the education community, especially teachers and school principals, were required to master "new literacy" which was an addition to the old literacy (calistung). New literacy includes data literacy, technology and HR. In the face of the industrial revolution 4.0 teachers and principals must be able to master the digital technology that is developing at this time and improve their competencies to educate the current millennial generation. Revousi industry 4.0 has its own challenges that we must conquer such as by creating innovative and responsive resources for rapidly evolving technology. In addition, it is also necessary to adjust the facilities and infrastructure in learning, including information technology, the internet, data analysis, and computers. Principals and professional teachers must be able to educate the current millennial generation with a human digital skill approach or ability to be able to compete in the global world of the industrial revolution 4.0 era.